Method for evaluating sulfate freezing and thawing resistance of recycled coarse aggregate self-compacting concrete
By conducting freeze-thaw cycle tests in a sulfate freeze-thaw environment, the damage indicators of self-finished concrete of regenerated crude aggregate were measured, which solved the problem of poor durability in a sulfate freeze-thaw environment, and achieved accurate evaluation of its performance and improved durability.
Patent Information
- Application Number
- CN202411799953.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-11
AI Technical Summary
The poor durability of recycled coarse aggregate self-finished concrete in sulfate freeze-thaw environments limits its engineering application in the load-bearing structure.
An evaluation method is used to measure and compare the damage indicators of the specimen such as mass loss rate, dynamic elastic modulus damage value and ultrasonic wave velocity damage value by preparing regenerated coarse aggregate self-finishing concrete specimens and conducting freeze-thaw cycle tests in different freeze-thaw environments to evaluate its anti-sulfate freeze-thaw performance.
This method can accurately evaluate the performance changes of regenerated coarse aggregate self-finished concrete in sulfate freeze-thaw environment, providing theoretical basis and technical support to improve its durability and engineering applications.
Smart Images

Figure CN119804535A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material testing and relates to a method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete. Background Art
[0002] So far, many scholars have conducted extensive research on the production of recycled concrete with recycled aggregates. Recycled concrete has been used in engineering. In previous studies, the research topic of combining recycled concrete with self-compacting concrete has attracted the attention of many scholars. Self-compacting concrete can completely fill every corner of the formwork without vibration during the pouring process. It is a high-performance concrete with the advantages of compactness, stability and homogeneity. Self-compacting concrete has been widely used in structures with dense reinforcement and complex shapes. Recycled coarse aggregate self-compacting concrete is a high-performance green concrete with self-compacting concrete function that uses recycled coarse aggregate obtained by crushing, screening and grading waste concrete to replace stone. In recent years, many scholars have studied recycled coarse aggregate self-compacting concrete. In general, using recycled coarse aggregate to replace stone will reduce the working performance, mechanical properties and durability of recycled coarse aggregate self-compacting concrete. This is because recycled coarse aggregate has higher water absorption, larger crushing index and irregular particle shape than stone. The performance defects of recycled coarse aggregate limit the engineering application of recycled coarse aggregate self-compacting concrete in load-bearing structures.
[0003] Sulfate attack and freeze-thaw cycles are two adverse environmental problems that hydraulic concrete structures often encounter, and are also one of the main causes of concrete aging. Compared with the durability damage under the influence of a single factor, the damage caused by sulfate attack and freeze-thaw cycle coupling (i.e., sulfate freeze-thaw effect) to concrete is more serious and the damage mechanism is more complicated. When sulfate freeze-thaw acts on concrete, the degree of damage to the concrete is not a simple superposition of destructive effects, but a mutual promotion or inhibition of the two destructive effects. Therefore, the study of the effect of sulfate freeze-thaw on concrete cannot simply rely on experience to determine the damage effect, but also needs to be concluded through experimental research. Due to the full recognition of the weakening effect of sulfate freeze-thaw on the durability of concrete, many scholars have carried out some research on the sulfate freeze-thaw resistance of concrete and have also achieved some research results. Jia (Jia P, Li L, Zhou J, et al. Performance Evolution of Recycled Aggregate Concrete under the Coupled Effect of Freeze-Thaw Cycles and Sulfate Attack[J]. Applied Sciences, 2022, 12(14): 1-14.) studied the effect of sulfate freeze-thaw on the durability of high-performance recycled concrete. The results showed that the high porosity of recycled coarse aggregate is the main factor that makes recycled concrete more susceptible to freeze-thaw damage and sulfate attack. Niu studied the sulfate freeze-thaw erosion test on concrete (Niu D, Jiang L, Fei Q. Deterioration mechanism of sulfate attack on concrete under freeze-thaw cycles [J]. Journal of Wuhan University of Technology-Mater. Sci. Ed., 2013, 28 (6): 1172-1176.). The results showed that the erosion products produced by concrete under the erosion of sulfate freeze-thaw are mainly ettringite and gypsum; the formation of substances such as ettringite and gypsum will consume a large amount of calcium hydroxide in the hydration products of concrete, thereby reducing the pH value of concrete and causing the decomposition of the hydration products of concrete (Tian B, Cohen M D. Does gypsum formation during sulfate attack on concrete lead to expansion? [J]. Cement and concrete research, 2000, 30 (1): 117-123.).
[0004] Self-compacting concrete with recycled coarse aggregate has limited structural applications worldwide. The poor durability of self-compacting concrete with recycled coarse aggregate affects the long-term safe use and service life of self-compacting concrete with recycled coarse aggregate in engineering applications in load-bearing structures. Many scholars have conducted some research on the damage of self-compacting concrete with recycled coarse aggregate after a single durability damage. Tuyan's research results (Tuyan M, Mardani-Aghabaglou A, Ramyar K. Freeze-thaw resistance, mechanical and transport properties of self-consolidating concrete incorporating coarse recycled concrete aggregate[J]. Materials&Design, 2014, 53: 983-991.) show that when the recycled coarse aggregate replacement rate of self-compacting concrete with recycled coarse aggregate is 100%, the self-compacting concrete with recycled coarse aggregate will suffer severe damage and cracks after 300 cycles of freeze-thaw. However, Huda's research results (Huda SB, Shahria Alam M. Mechanical and freeze-thaw durability properties of recycled aggregate concrete made with recycled coarse aggregate [J]. Journal of Materials in Civil Engineering, 2015, 27 (10): 1-9.) show that the use of recycled coarse aggregate instead of stone has a certain effect on enhancing the pore characteristics of recycled coarse aggregate self-compacting concrete, which may lead to enhanced frost resistance. Modani's research results (Modani PO, Mohitkar V M. Self-compacting concrete with recycled aggregate: A solution for sustainable development [J]. International Journal of Civil & Structural Engineering, 2014, 4 (3): 430-440.) show that the carbonation depth has a good linear correlation with the compressive strength.
[0005] At present, there have been some achievements in the research on the durability damage of recycled coarse aggregate self-compacting concrete under the influence of a single factor, but there are few studies on the durability damage of recycled coarse aggregate self-compacting concrete under the coupling of multiple factors, and there is also a lack of reports on the scheme that can objectively evaluate the durability damage results of recycled coarse aggregate self-compacting concrete under the coupling of multiple factors. The present invention is proposed based on this. Summary of the invention
[0006] The purpose of the present invention is to provide a method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete, which can accurately evaluate the effects of different recycled coarse aggregate replacement rates, different freeze-thaw environments and multiple freeze-thaw cycles on the performance of recycled coarse aggregate self-compacting concrete, in order to provide a theoretical basis and technical support for improving the durability and engineering application of recycled coarse aggregate self-compacting concrete in a sulfate freeze-thaw environment.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] A method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete comprises the following steps:
[0009] S1. Prepare recycled coarse aggregate self-compacting concrete specimens in which recycled coarse aggregate completely or partially replaces stone according to design requirements;
[0010] S2, immersing the recycled coarse aggregate self-compacting concrete specimens in a freeze-thaw medium to conduct a freeze-thaw cycle test;
[0011] S3, measuring damage indicators of recycled coarse aggregate self-compacting concrete specimens, wherein the damage indicators include mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting tensile strength, stress-strain curve, elastic modulus or Poisson's ratio;
[0012] S4. Compare the damage indicators of self-compacting concrete specimens with different recycled coarse aggregates to obtain recycled coarse aggregate self-compacting concrete specimens with excellent comprehensive performance.
[0013] Furthermore, in S2, the freeze-thaw medium includes water, a 5% by mass Na2SO4 solution, a 5% by mass MgSO4 solution, and a mixed salt solution of 5% by mass Na2SO4 and 5% by mass MgSO4.
[0014] Furthermore, in S2, the freeze-thaw cycle test was performed using a HDK-3 concrete rapid freeze-thaw machine according to the rapid freezing method to ensure that the specimens were always in a saturated freeze-thaw medium state during the freeze-thaw process.
[0015] Furthermore, in S3, the calculation formulas for the mass loss rate, the dynamic elastic modulus damage value, and the ultrasonic wave velocity damage value are respectively:
[0016]
[0017] Where, ΔW N is the mass loss rate after N freeze-thaw cycles, in %; G0 and G N are the mass of recycled coarse aggregate self-compacting concrete before and after the freeze-thaw cycle test N times, in kg; D N is the dynamic elastic modulus damage value after freeze-thaw cycles N times; E0 and E N are the dynamic elastic modulus of recycled coarse aggregate self-compacting concrete before the freeze-thaw cycle test and after N freeze-thaw cycles, in MPa; V N V is the ultrasonic wave velocity damage value after N freeze-thaw cycles; d0 and V dN are the ultrasonic wave velocities of recycled coarse aggregate self-compacting concrete before and after the freeze-thaw cycle test N times, in km·s -1 .
[0018] Furthermore, in S3, the compressive strength is tested using a SHT4106 microcomputer-controlled electro-hydraulic servo universal testing machine; the splitting strength is tested using a CMT5305 microcomputer-controlled electro-hydraulic servo universal testing machine; and the stress-strain curve, elastic modulus and Poisson's ratio are all tested using a SHT4106 microcomputer-controlled electro-hydraulic servo universal testing machine.
[0019] Further, in S4, the evaluation standard for the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen is as follows: the evaluation standard for the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen is as follows: the smaller the mass loss rate, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen; the smaller the dynamic elastic modulus damage value, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen; the smaller the ultrasonic wave velocity damage value, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen; the greater the compressive strength, splitting tensile strength and uniaxial compressive strength, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen; the smoother the change of the stress-strain curve, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen; the larger the elastic modulus and Poisson's ratio, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen.
[0020] The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1 is characterized in that, in S4, a durability comprehensive evaluation index of RCASCC is defined based on the principle of entropy weight method. The calculation formula of the durability comprehensive evaluation index is as follows:
[0021]
[0022] Where: D is a comprehensive durability evaluation index. i is the weight of the i-th durability indicator. i is the normalized value of the ith durability indicator.
[0023] There are various methods for evaluating the durability of concrete, and different standards are used by different institutions. When concrete is subjected to sulfate freeze-thaw in actual environments, multiple performance indicators will change. Therefore, it is crucial to establish a comprehensive evaluation system to evaluate the durability of concrete. The setting of weights plays a key role in the accuracy of the evaluation results in the comprehensive evaluation of multiple indicators. In order to comprehensively evaluate its durability, it is necessary to comprehensively consider the comprehensive impact of each indicator and pay attention to the differences in the degree of influence of each indicator. Therefore, the comprehensive evaluation index of durability is defined based on the entropy weight method theory.
[0024] (1) Initial durability index matrix.
[0025]
[0026] Among them, A=[a ij ] uv is the initial durability index matrix. ij is the first j The value of the durability index. u and v represent the number of evaluation objects and durability indexes respectively.
[0027] (2) Standardization of durability indicators.
[0028]
[0029] Where W = [w ij ] u×v is the standardized durability index matrix. ij is a ij The standard value of .
[0030] (3) Establish a weight matrix.
[0031]
[0032] Where Q = [q ij ] u×v is the weight matrix. ij is a ij proportion.
[0033] (4) Establish information utility value matrix.
[0034]
[0035] Where P = [p j ] 1×vis the information utility value matrix. j It is j The information utility value of an indicator.
[0036] (5) Establish an indicator weight matrix.
[0037]
[0038] Where K = [k j ] 1×j is the indicator weight matrix. k j is the weight of the jth indicator.
[0039] (6) Comprehensive evaluation index matrix.
[0040]
[0041] Where D is the durability evaluation index matrix of recycled coarse aggregate self-compacting concrete under sulfate freeze-thaw action. i It is an evaluation index of the durability of recycled coarse aggregate self-compacting concrete under the action of sulfate freeze-thaw.
[0042] Furthermore, in the present invention, the calculation formula of the durability comprehensive evaluation index D is:
[0043] D=q1S1+q2S2+q3S3+q4S4+q5S5+q6S6+q7S7;
[0044] Among them, q1, q2, q3, q4, q5, q6, and q7 are the weight coefficients of S1 to S7, and their values are 0.1348, 0.1443, 0.136, 0.1372, 0.1644, and 0.1427 respectively;
[0045] S1 to S7 represent the values of mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting strength, elastic modulus and Poisson's ratio, respectively.
[0046] And during the evaluation process, the smaller the D value is, the worse the comprehensive sulfate freeze-thaw resistance is.
[0047] More specifically, when the D value is less than 0.75, it indicates that the recycled coarse aggregate self-compacting concrete specimen is damaged.
[0048] Compared with the prior art, the present invention designs a sulfate freeze-thaw resistance test scheme for recycled coarse aggregate self-compacting concrete from three aspects: freeze-thaw cycle number, recycled coarse aggregate replacement rate and freeze-thaw environment. Then a series of damage indicators are tested and calculated, such as surface characteristics, failure morphology, mass loss rate, dynamic elastic modulus damage value and ultrasonic wave velocity damage value. Studying the performance changes of recycled coarse aggregate self-compacting concrete after sulfate freeze-thaw has certain theoretical guidance and exploratory significance for the engineering practice of recycled coarse aggregate self-compacting concrete in severe cold and sulfate-rich environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Appearance of materials: (a) NCA. (b) RCA. (c) Na2SO4 powder. (d) MgSO4 powder.
[0050] Figure 2 Particle size distribution for cement, NCA, RCA, large stones, small stones and sand.
[0051] Figure 3 is the temperature curve of the specimen and the heat conducting medium.
[0052] Figure 4 This is the distribution diagram of measurement points during the dynamic elastic modulus test.
[0053] Figure 5 This is the distribution diagram of measurement points during the ultrasonic wave velocity test.
[0054] Figure 6 For compressive and splitting strength testing.
[0055] Figure 7 This is the curve of D changing with the number of sulfate freeze-thaw cycles.
[0056] Figure 8 The surface characteristics of recycled coarse aggregate self-compacting concrete before and after sulfate freeze-thaw.
[0057] Fig. 9 This is the failure morphology of recycled coarse aggregate self-compacting concrete before and after sulfate freeze-thaw.
[0058] Fig.10 This is the relationship curve between mass loss rate and the number of sulfate freeze-thaw cycles.
[0059] Fig.11 This is the relationship curve between the dynamic elastic modulus damage value and the number of sulfate freeze-thaw cycles.
[0060] Fig.12 This is the relationship curve between the ultrasonic wave velocity damage value and the number of sulfate freeze-thaw cycles.
[0061] Fig.13 This is the relationship curve between compressive strength and the number of sulfate freeze-thaw cycles.
[0062] Fig.14 This is the relationship curve between splitting tensile strength and the number of sulfate freeze-thaw cycles.
[0063] Fig.15 This is the stress-strain curve of self-compacting concrete with recycled coarse aggregate after sulfate freeze-thaw.
[0064] Fig.16 These are the stress-strain curves of recycled coarse aggregate self-compacting concrete after different times of sulfate freeze-thaw.
[0065] Fig.17 is the variation trend of peak stress with peak strain.
[0066] Fig.18 is the relationship between relative peak stress and the number of sulfate freeze-thaw cycles.
[0067] Fig.19 is the relationship between relative peak strain and the number of sulfate freeze-thaw cycles.
[0068] Fig. 20 is the relationship between the ultimate strain and the number of sulfate freeze-thaw cycles.
[0069] Fig.21 Comparison of the fitted curve and the experimental curve.
[0070] Fig. 22 is the variation of parameters with peak stress.
[0071] Fig.23 is the relationship between the elastic modulus and the number of freeze-thaw cycles of sulfate.
[0072] Fig.24 is the relationship between Poisson's ratio and the number of sulfate freeze-thaw cycles.
[0073] Fig.25 is the relationship between peak stress and dynamic elastic modulus.
[0074] Fig.26 is the relationship between peak stress and ultrasonic wave velocity. DETAILED DESCRIPTION
[0075] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0076] In order to evaluate the effects of different recycled coarse aggregate replacement rates, different freeze-thaw environments and multiple freeze-thaw cycles on the performance of recycled coarse aggregate self-compacting concrete, the present invention provides a method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete, comprising the following steps:
[0077] S1. Prepare recycled coarse aggregate self-compacting concrete specimens in which recycled coarse aggregate completely or partially replaces stone according to design requirements;
[0078] S2, immersing the recycled coarse aggregate self-compacting concrete specimens in a freeze-thaw medium to conduct a freeze-thaw cycle test;
[0079] S3, measuring damage indicators of recycled coarse aggregate self-compacting concrete specimens, wherein the damage indicators include mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting tensile strength, uniaxial compressive strength, stress-strain curve, elastic modulus or Poisson's ratio;
[0080] S4. Compare the damage indicators of self-compacting concrete specimens with different recycled coarse aggregates to obtain recycled coarse aggregate self-compacting concrete specimens with excellent comprehensive performance.
[0081] The following is a further detailed description of the sulfate freeze-thaw resistance evaluation method of recycled coarse aggregate self-compacting concrete and the test method according to the present invention in combination with specific data.
[0082] Embodiment 1:
[0083] Test Materials:
[0084] The cement is ordinary Portland cement (PO42.5) produced by a local cement plant, and the density of cement is 3.15g / cm 3 The initial and final setting times were 142 min and 198 min respectively, and the 3d and 28d compressive strengths were 28.2 MPa and 48.7 MPa respectively.
[0085] The sand was washed medium sand from Lanshan Sand and Gravel Field in Yinchuan City. The apparent density, bulk density, porosity, mud content and fineness modulus of the sand were 2718 kg·m -3 、1630kg·m -3 , 40%, 1.2% and 2.94.
[0086] The test water is city tap water. The water reducer is a powdered polycarboxylic acid high performance water reducer.
[0087] The appearance of the water reducer is light gray, the water reduction rate is about 32%, the density is 500-600g / L, the solid content is 98±1%, the pH is 6-8, the chloride ion content is ≤0.01%, and the sulfate ion content is about 2.6%. It is a standard HWR-S polycarboxylic acid high-performance water reducer (powder) produced by Beijing Muhu Admixture Co., Ltd.
[0088] NCA (gravel) comes from Yinchuan Lanshan Sand and Gravel Factory. Gravel (NCA) includes two types, large gravel and small gravel. The gravel particle size is 10-20mm, and the small gravel particle size is 5-10mm. Large gravel and small gravel are mixed in a mass ratio of 7:3.
[0089] The recycled coarse aggregate (RCA) required for the test is made of discarded road slab concrete, and the gradation is designed to be the same or approximately the same as that of gravel.
[0090] The appearance of sodium sulfate (Na2SO4) powder is white crystalline powder, which is hygroscopic, soluble in water and insoluble in ethanol.
[0091] The appearance of magnesium sulfate (MgSO4) powder is colorless crystal or white crystalline powder, tastes salty and bitter, is soluble in water and glycerin, slightly soluble in ethanol, and insoluble in acetone.
[0092] The performance parameters of NCA and RCA are shown in Table 1. The performance parameters of Na2SO4 and MgSO4 powders are shown in Table 2. The appearance of NCA, RCA, Na2SO4 powder and MgSO4 powder is shown in Table 3. Figure 1 The particle size distribution of cement, NCA, RCA, large stone, small stone and sand is as follows: Figure 2 shown.
[0093] Table 1 Performance parameters of NCA and RCA
[0094]
[0095] Table 2 Performance parameters of Na2SO4 and MgSO4 powders
[0096] category Relative molecular weight content / % pH Insoluble matter / % Cl / % <![CDATA[PO4 / %]]> <![CDATA[Sodium sulfate powder]]> 142.04 ≥99.0 5-8 ≤0.005 ≤0.001 ≤0.001 <![CDATA[MgSO4 powder]]> 120.37 ≥99.0 5-8 ≤0.005 ≤0.002 ≤0.005
[0097] Table 3 shows the mix proportion of recycled coarse aggregate self-compacting concrete. This embodiment experimentally designed four freeze-thaw environments, which are water, 5% mass fraction Na2SO4 salt solution, 5% mass fraction MgSO4 salt solution, and a mixed salt solution of 5% mass fraction Na2SO4 and 5% mass fraction MgSO4. For the convenience of subsequent writing, this embodiment uses letters H, N, M and NM to represent these four freeze-thaw environments respectively. The experiment designed six freeze-thaw cycle times (0, 25, 50, 75, 100 and 125 times). The experiment designed three RCA replacement rates (0, 50% and 100%).
[0098] Table 3 Mix proportion of recycled coarse aggregate self-compacting concrete
[0099]
[0100] Freeze-thaw cycle test. After the specimen is cured, immerse it in water at 20±2℃ for 4 days. To ensure that the specimen is always saturated with water during freezing and thawing, the water surface of the specimen should be 20-30mm higher than the specimen. After the immersion is completed, put the specimen into a rubber barrel. Add clean water, or 5% mass fraction Na2SO4 solution, or 5% mass fraction MgSO4 solution, or a mixed salt solution of 5% mass fraction Na2SO4 and 5% mass fraction MgSO4 into the barrel. Finally, put the barrel into the freeze-thaw machine, start the machine to start the freeze-thaw cycle test. The test method of the freeze-thaw cycle test is the quick freezing method, and the test instrument is the HDK-3 concrete quick freeze-thaw machine. Figure 3 This is a working diagram of the freeze-thaw machine.
[0101] Mass, dynamic elastic modulus and ultrasonic wave velocity test. The mass of the specimen is measured using an electronic scale with a sensitivity of 1g and a range of 30kg. The dynamic elastic modulus of the specimen is measured using a DT-20 dynamic elastic modulus tester. Figure 4 The figure is a schematic diagram of dynamic elastic modulus testing. There are 4 groups of measuring points in total. The final test result is the average value of the 4 groups of measuring points. The ultrasonic wave velocity of the specimen is measured using a DJUS-05 non-metallic ultrasonic instrument. Figure 5 This is a schematic diagram of ultrasonic wave velocity detection. There are 5 groups of measurement points in total. The final test result is the average value of the 5 groups of measurement points.
[0102] The mass damage rate of recycled coarse aggregate self-compacting concrete is calculated using formula (1). The dynamic elastic modulus damage value of recycled coarse aggregate self-compacting concrete is calculated using formula (2). The ultrasonic wave velocity damage value of recycled coarse aggregate self-compacting concrete is calculated using formula (3).
[0103]
[0104]
[0105] Where, ΔW N is the mass loss rate after N freeze-thaw cycles, in %; G0 and G N are the mass of recycled coarse aggregate self-compacting concrete before and after the freeze-thaw cycle test N times, in kg; D N is the dynamic elastic modulus damage value after freeze-thaw cycles N times; E0 and E N are the dynamic elastic modulus of recycled coarse aggregate self-compacting concrete before the freeze-thaw cycle test and after N freeze-thaw cycles, in MPa; V N V is the ultrasonic wave velocity damage value after N freeze-thaw cycles; d0 and V dN are the ultrasonic wave velocities of recycled coarse aggregate self-compacting concrete before and after the freeze-thaw cycle test N times, in km·s-1 .
[0106] Compression and splitting strength test. The compressive strength of the test specimens was tested using a SHT4106 microcomputer-controlled electro-hydraulic servo universal testing machine. The maximum load of the testing machine is 1000KN, and the accuracy is 0.001N. During the test, the loading method of the testing machine is stress loading, and the loading speed is 0.5MPa·s -1 The actual operation diagram of compressive strength test is shown in Figure 6 (a). The splitting tensile strength of the test specimen was tested using a CMT5305 microcomputer-controlled electro-hydraulic servo universal testing machine. The maximum load of the testing machine is 300KN and the loading speed is 0.05MPa·s -1 The actual operation diagram of splitting strength test is shown in Figure 6 (b).
[0107] Stress-strain curve, elastic modulus and Poisson's ratio test. The stress-strain curve, elastic modulus and Poisson's ratio of the specimen were tested using a SHT4106 microcomputer-controlled electro-hydraulic servo universal testing machine. Stress loading was selected as the loading method of the testing machine. The loading rate of the testing machine was set to 0.5 MPa·s when measuring stress-strain. -1 When measuring the elastic modulus and Poisson's ratio, the loading rate of the testing machine was set to 0.05 MPa·s -1 . The strain data was collected using a JM3813 multifunctional static strain gauge. The strain gauge has a resolution of 0.5με, a range of ±15000με, and an accuracy of ±0.2%FS±1με. The displacement sensor used was a 5G101 displacement sensor. The displacement sensor has a sensitivity of 90με / mm, a range of 60mm, and an accuracy of 0.3%FS. The lengths of the strain gauges are 100mm and 50mm, and they are placed crosswise in a "+" shape. The resistance of the strain gauge is 120Ω, and the sensitivity coefficient is 2.08%.
[0108] By observing the changes in the apparent characteristics of recycled coarse aggregate self-compacting concrete, we can intuitively understand the damage of recycled coarse aggregate self-compacting concrete. Figure 8 The surface characteristics of recycled coarse aggregate self-compacting concrete before and after sulfate freeze-thaw. Figure 8 The size of the recycled coarse aggregate self-compacting concrete shown is 100mm×100mm×300mm. Figure 8It can be seen that the damage caused by sulfate freeze-thaw to recycled coarse aggregate self-compacting concrete is a gradual process. With the increase of the number of freeze-thaw cycles, the surface condition of recycled coarse aggregate self-compacting concrete gradually deteriorates. At 0 freeze-thaw cycles, the surface of recycled coarse aggregate self-compacting concrete was smooth and flat without damage. After 50 freeze-thaw cycles, a small amount of mortar fell off and slightly pockmarked the surface of recycled coarse aggregate self-compacting concrete, and the distribution was sparse, but the appearance was relatively intact. After 125 freeze-thaw cycles, the surface of recycled coarse aggregate self-compacting concrete became uneven, and the edges and corners were partially damaged. In the H-type freeze-thaw environment and the same number of freeze-thaw cycles, the greater the RCA replacement rate, the more serious the surface deterioration of recycled coarse aggregate self-compacting concrete. When the RCA replacement rate is 50% and the number of freeze-thaw cycles is the same, the surface deterioration of recycled coarse aggregate self-compacting concrete under M freeze-thaw environment is the most serious, the damage to recycled coarse aggregate self-compacting concrete under H freeze-thaw environment is the slightest, and the apparent characteristics of recycled coarse aggregate self-compacting concrete under N and NM freeze-thaw environments are slightly different.
[0109] The stress-strain curve of recycled coarse aggregate self-compacting concrete was tested. Fig. 9 This is the failure morphology of recycled coarse aggregate self-compacting concrete before and after sulfate freeze-thaw. Fig. 9 The size of the recycled coarse aggregate self-compacting concrete on display is 100mm×100mm×300mm. Taking the NC-H-0 group recycled coarse aggregate self-compacting concrete as an example, the loading and failure process of the recycled coarse aggregate self-compacting concrete is described. Through observation tests, it can be seen that when the load is initially applied, there is no visible change on the surface of the recycled coarse aggregate self-compacting concrete, and the load increases approximately in proportion to time. As the load gradually increases, a small number of oblique fine cracks begin to appear in the middle and corners of the recycled coarse aggregate self-compacting concrete, and gradually expand into cracks; at this time, the load-time relationship curve gradually flattens. As the load further increases, the cracks begin to widen and become more numerous, and the cracks develop in the longitudinal and oblique directions. When the load increases to 0.8-0.9 times the peak load, the volume deformation of the recycled coarse aggregate self-compacting concrete reaches the maximum value, and the number of cracks gradually increases. After the load exceeds the peak load, the volume deformation of the recycled coarse aggregate self-compacting concrete gradually recovers, the bearing capacity gradually decreases, and the oblique cracks form through long cracks under the action of normal stress and shear stress. Finally, the recycled coarse aggregate self-compacting concrete was unstable and destroyed. Accompanied by a splitting sound, the recycled coarse aggregate self-compacting concrete was split into several irregularly shaped concrete blocks. The failure morphology of the NC-H-0 group recycled coarse aggregate self-compacting concrete showed the characteristics of oblique shear failure.
[0110] The damage caused by sulfate freeze-thaw to concrete is similar to that caused by freeze-thaw, but it also has its own unique characteristics. With the increase of freeze-thaw cycles, the surface cracks of recycled coarse aggregate self-compacting concrete after destruction gradually increase, the plastic deformation tends to be serious, and the failure mode gradually changes from shear failure to internal splitting and tensile failure of recycled coarse aggregate self-compacting concrete. In the H-type freeze-thaw environment and the same number of freeze-thaw cycles, the greater the RCA replacement rate, the more surface cracks of recycled coarse aggregate self-compacting concrete after destruction, and the more serious the failure mode. Compared with NCA, RCA has lower apparent density, higher bulk density, higher void ratio, higher porosity, higher water content, and higher crushing index. The physical properties of RCA are weaker than NCA. Using RCA to replace NCA to mix concrete will weaken the durability of concrete to a certain extent. At 50% RCA replacement rate and the same number of freeze-thaw cycles, the failure mode of recycled coarse aggregate self-compacting concrete in the H-type freeze-thaw environment is the lightest, and the failure mode of recycled coarse aggregate self-compacting concrete in the N, M and NM freeze-thaw environments is not much different. Sulfate itself can cause concrete corrosion, which can aggravate the damage to concrete. Secondly, the hygroscopicity and water saturation of sulfate increase the saturation, frozen water volume and frost heave force of concrete, thereby accelerating the destruction of concrete, making the degree of damage to recycled coarse aggregate self-compacting concrete in N, M and NM freeze-thaw environments greater than that of H. At the same time, sulfate can lower the freezing point of the pore solution, thereby reducing the damage caused by sulfate freeze-thaw to recycled coarse aggregate self-compacting concrete.
[0111] The calculated mass loss rate is used to draw a curve of the relationship between the mass loss rate and the number of freeze-thaw cycles, such as Fig.10 shown. Fig.10 It shows that with the increase of freeze-thaw cycles, the mass loss of recycled coarse aggregate self-compacting concrete first decreases and then increases; after 125 freeze-thaw cycles, the mass loss rate of recycled coarse aggregate self-compacting concrete is less than 5%; at 0-50 freeze-thaw cycles, the mass loss rates of RC50 and R100 are negative; at 0-50 freeze-thaw cycles, the surface mortar shedding and internal pore erosion of recycled coarse aggregate self-compacting concrete are relatively slight, and at this time, the recycled coarse aggregate self-compacting concrete absorbs a large amount of water, causing the mass loss rate to be negative; with the increase of freeze-thaw cycles, the mass loss rate gradually increases, and the growth rate also gradually accelerates; Fig.10 (a) shows that when the RCA replacement rate is larger, the mass loss rate of recycled coarse aggregate self-compacting concrete is larger and the growth rate is faster. Fig.10(b) shows that the different freeze-thaw environments have little effect on the mass loss rate of recycled coarse aggregate self-compacting concrete. After 125 freeze-thaw cycles, the mass loss rates of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM are 0.34%, 0.36%, 0.38%, 0.38%, 0.41% and 0.39%, respectively. The mass loss rate is one of the important indicators to measure the durability of concrete. By analyzing the relationship between the mass loss rate and the number of freeze-thaw cycles, the durability of recycled coarse aggregate self-compacting concrete after long-term freeze-thaw can be evaluated, thereby predicting its service life. At the same time, the relationship curve between the mass loss rate and the number of freeze-thaw cycles is helpful to identify the influence of different RCA (recycled coarse aggregate) replacement rates on concrete performance, and then optimize the concrete mix ratio. The study shows that the greater the RCA replacement rate, the greater the mass loss rate and the faster the growth rate, which provides a scientific basis for adjusting the use ratio of RCA. By analyzing the changes in mass loss rate under different freeze-thaw environments, the adaptability of concrete to different environments can be evaluated. For example, the study found that the freeze-thaw environment has little effect on the mass loss rate, which indicates that the performance of concrete is relatively stable under specific environments.
[0112] The calculated dynamic elastic modulus damage value is used to draw a curve of the relationship between the dynamic elastic modulus damage value and the number of freeze-thaw cycles, such as Fig.11 shown. Fig.11 It shows that with the increase of freeze-thaw cycles, the dynamic elastic modulus damage value of recycled coarse aggregate self-compacting concrete gradually increases; the change curve of the dynamic elastic modulus damage value of recycled coarse aggregate self-compacting concrete with the number of freeze-thaw cycles can be divided into three stages, namely the steady growth stage, the linear growth stage and the relatively stable stage; after 125 freeze-thaw cycles, the dynamic elastic modulus damage values of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM increased to 0.3025, 0.3207, 0.4555, 0.3495, 0.3812 and 0.3606 respectively. After 125 freeze-thaw cycles, the dynamic elastic modulus damage value of RC100-H was greater than 0.4, indicating that RC100-H was damaged.
[0113] The dynamic elastic modulus damage value and the number of freeze-thaw cycles conform to a logarithmic function relationship, as shown in formula (4). The fitting curve is shown in Fig.11 From formula (4), we can see that the correlation coefficient R 2 All are greater than 0.9104, indicating that the fitting accuracy is high. Fig.11 In the figure, the data points are all distributed near the fitting curve, which shows that the fitting results have good correlation.
[0114]
[0115] Fig.12This is the relationship curve between the ultrasonic wave velocity damage value and the number of freeze-thaw cycles. Fig.12 It can be seen that with the increase of the number of freeze-thaw cycles, the ultrasonic wave velocity damage value of recycled coarse aggregate self-compacting concrete gradually increases; the change curve of the ultrasonic wave velocity damage value of recycled coarse aggregate self-compacting concrete with the number of freeze-thaw cycles can be divided into three stages, namely, a relatively stable stage, a linear growth stage and a steady growth stage; after 125 freeze-thaw cycles, the ultrasonic wave velocity damage values of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM increased to 0.4587, 0.4649, 0.5061, 0.5241, 0.562 and 0.5321 respectively.
[0116] The ultrasonic wave velocity damage value and the number of freeze-thaw cycles conform to an exponential function relationship, as shown in formula (5). The fitting curve is shown in Fig.12 From formula (5), it can be seen that the fitting curve obtained has high fitting accuracy, and the highest correlation coefficient is 0.9934. The data points are distributed near the fitting curve, indicating that the fitting result is good and has certain reference value.
[0117]
[0118] Fig.13 It is the relationship curve between compressive strength and freeze-thaw cycle number. Fig.13 It can be seen that with the increase of freeze-thaw cycles, the compressive strength of each group of recycled coarse aggregate self-compacting concrete decreases. Fig.13 (a) is the relationship curve between different RCA substitution rates and compressive strength. Fig.13 (a) It can be seen that at 0 freeze-thaw cycles, the compressive strength difference between NC-H and RC50-H is large, and the compressive strength difference between RC50-H and RC100-H is small; the strength and elastic modulus of RCA are weaker than those of NCA, which makes the compressive strength of RC50-H and RC100-H weaker than that of NC-H; when the ratio of RCA replacing NCA is large, the actual water-binder ratio of recycled coarse aggregate self-compacting concrete increases due to the large amount of water absorbed by RCA, making the compressive strength difference between RC50-H and RC100-H smaller; each group of curves shows obvious "stratification phenomenon"; after 125 freeze-thaw cycles, the compressive strength loss rates of NC-H, RC50-H and RC100-H are 10.63%, 15.26% and 20.24% respectively. Fig.13 (b) is the relationship curve between different freeze-thaw environments and compressive strength. Fig.13(b) It can be seen that the compressive strength of RC50-H and RC50-N decreases faster after 75 freeze-thaw cycles, and the compressive strength of RC50-M and RC50-NM decreases faster after 25 freeze-thaw cycles; the difference in compressive strength of RC50 after 25 and 50 freeze-thaw cycles under the four freeze-thaw environments is small, and the difference gradually increases after more than 50 times; after 125 freeze-thaw cycles, the compressive strength loss rates of RC50-H, RC50-N, RC50-M and RC50-NM are 15.26%, 18.42%, 23.03% and 19.29% respectively.
[0119] During the freeze-thaw process, the free water volume in the pores of recycled coarse aggregate self-compacting concrete will expand and contract, thereby reducing the structural stability of recycled coarse aggregate self-compacting concrete. With the increase in the number of freeze-thaw cycles, new microcracks will continue to generate and develop, and damage will continue to accumulate. Compared with NC, the bonding performance between the old mortar layer inside RC50 and RC100 and the matrix is poor. Poor bonding performance will make RC50 and RC100 have poorer anti-freeze performance when facing freeze-thaw damage compared with NC.
[0120] During freezing and thawing, SO4 2- It reacts with Ca(OH)2 in the hydration substances in the recycled coarse aggregate self-compacting concrete to form gypsum (CaSO4·2H2O), which reduces the content of hydration substances and the bonding strength between aggregate and cement paste, causing the recycled coarse aggregate self-compacting concrete to collapse or peel off, affecting the overall structure. 2- It can also react with calcium sulfoaluminate (3CaO·Al2O3·12H2O) to form ettringite (3CaO·Al2O3·3CaSO4·32H2O) and Al(OH)3, which are easy to absorb water and expand. Under the combined effects of freeze-thaw and sulfate erosion, the expansion of the expansive substances inside the recycled coarse aggregate self-compacting concrete, the freezing of the solution, the crystallization of salt, and the decrease in the bonding force between the aggregate and the cement paste will cause irreversible residual expansion deformation in the cracks inside the recycled coarse aggregate self-compacting concrete, making the recycled coarse aggregate self-compacting concrete more fragile, which is manifested as a decrease in strength on a macro scale.
[0121] The measured splitting tensile strength is used to draw a curve of the relationship between the splitting tensile strength and the number of freeze-thaw cycles, such as Fig.14 As shown. Fig.14 It can be seen that with the increase of freeze-thaw cycles, the splitting tensile strength of each group of recycled coarse aggregate self-compacting concrete gradually decreases. Fig.14 (a) shows that the curves of NC-H, RC50-H and RC100-H show obvious "stratification phenomenon"; after 125 freeze-thaw cycles, the splitting strength loss rates of NC-H, RC50-H and RC100-H are 15.27%, 19.05% and 23.01%, respectively. Fig.14 (b) shows that among the four groups of recycled coarse aggregate self-compacting concrete, the splitting tensile strength of RC50-M decreases the fastest, while the splitting tensile strength decrease rates of RC50-H, RC50-N and RC50-NM are not much different; after 125 freeze-thaw cycles, the splitting tensile strength loss rates of RC50-H, RC50-N, RC50-M and RC50-NM are 19.05%, 21.96%, 28.04% and 19.84% respectively.
[0122] The original cracks of waste concrete will expand and new cracks will be generated during long-term use and crushing. The basic properties of RCA made of waste concrete as raw material, such as strength, elastic modulus and water absorption, are weaker than those of NCA. The addition of RCA to concrete will reduce the mechanical and durability properties. The pores and cracks in the old cement mortar on the surface of RCA will continue to extend under the action of sulfate freeze-thaw, which will have an adverse effect on the performance of RC50 and RC100. The higher the ratio of RCA replacing NCA, the more pores and cracks in the old cement mortar inside the recycled coarse aggregate self-compacting concrete, the more serious the damage after sulfate freeze-thaw, and the greater the loss rate of compressive strength and splitting strength.
[0123] Using the measured stress and strain data, the stress-strain curve of recycled coarse aggregate self-compacting concrete after sulfate freeze-thaw was plotted, such as Fig.15 As shown. Fig.15 It can be seen that the stress-strain curves of each group of recycled coarse aggregate self-compacting concrete are similar in shape in the upper half, but have certain differences in the lower half; with the increase in the number of freeze-thaw cycles, the peak point of the curve gradually shifts to the lower right, and the shape of the curve gradually changes from a high and narrow type to a short and wide type. This shows that the recycled coarse aggregate self-compacting concrete shows a trend of gradually loosening.
[0124] The stress-strain curves of recycled coarse aggregate self-compacting concrete after different times of sulfate freeze-thaw are shown in Figure 2. Fig.16 shown. Fig.16 It shows that under the same number of freeze-thaw cycles, with the increase of RCA replacement rate, the peak point of the curve gradually shifts to the lower right; the lower half of the stress-strain curve in N, M and NM freeze-thaw environments is more concave than that in H freeze-thaw environment; this is mainly related to the greater damage suffered by recycled coarse aggregate self-compacting concrete in sulfate freeze-thaw environment.
[0125] The relationship between peak stress and peak strain is a linear function. Linear fitting can be performed to obtain the fitting formula and fitting graph as shown in formula (6) and Fig.17 shown.
[0126]
[0127] Where: 0N and ε0N They are the peak stress and peak strain of recycled coarse aggregate self-compacting concrete after N freeze-thaw cycles.
[0128] The relative peak stress is the ratio of the peak stress of recycled coarse aggregate self-compacting concrete after N freeze-thaw cycles to the peak stress at 0 freeze-thaw cycles. Fig.18 is the relationship between relative peak stress and freeze-thaw cycle number. Fig.18 It can be seen that with the increase of freeze-thaw cycles, the relative peak stress of each group of recycled coarse aggregate self-compacting concrete gradually decreases; at the same freeze-thaw cycle number, the relative peak stress of NC-H is the largest, and the relative peak stress of RC50-M is the smallest. Compared with 0 freeze-thaw cycles, the relative peak stress of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM decreased by 10.67%, 13.14%, 18.11%, 16.32%, 21.85% and 17.33% respectively after 125 freeze-thaw cycles. The relative peak stress has a good linear correlation with the number of freeze-thaw cycles. The equation obtained by fitting is shown in formula (7).
[0129]
[0130] in: is the relative peak stress.
[0131] The relative peak strain is the ratio of the peak strain of recycled coarse aggregate self-compacting concrete after N freeze-thaw cycles to the peak strain at 0 freeze-thaw cycles. Fig.19 is a graph showing the relationship between relative peak strain and the number of freeze-thaw cycles. Fig.19 The results show that the relative peak strain of each group of recycled coarse aggregate self-compacting concrete increases with the increase of freeze-thaw cycles; at the same freeze-thaw cycles, the relative peak stress of RC50-M is the largest, and the relative peak stress of NC-H is the smallest. Compared with 0 freeze-thaw cycles, the relative peak strains of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM increased by 45.77%, 44.71%, 47.2%, 47.12%, 54.33% and 50.48% respectively after 125 freeze-thaw cycles. The relationship between the relative peak strain and the number of freeze-thaw cycles is a linear function. Formula (8) is obtained by fitting.
[0132]
[0133] in: is the relative peak strain.
[0134] The ultimate strain is taken as the stress of the descending section of the stress-strain curve is 0.5σ 0N The corresponding longitudinal strain. Fig. 20 is the relationship curve between the ultimate strain and the number of freeze-thaw cycles. Fig. 20 It can be seen that with the increase of freeze-thaw cycles, the ultimate strain of each group of recycled coarse aggregate self-compacting concrete generally shows a trend of first increasing, then decreasing, and then increasing. Fig. 20 (a) It can be seen that the curves of NC-H, RC50-H and RC100-H show a "stratification phenomenon"; compared with 0 freeze-thaw cycles, the ultimate strains of recycled coarse aggregate self-compacting concrete after 125 freeze-thaw cycles increased by 30.54%, 41.1% and 38.13% respectively. Fig. 20 (b) It can be seen that the curves of RC50-H, RC50-N, RC50-M and RC50-NM are "entangled" together; compared with 0 freeze-thaw cycles, after 125 freeze-thaw cycles, the ultimate strains of RC50-H, RC50-N, RC50-M and RC50-NM of recycled coarse aggregate self-compacting concrete increased by 41.1%, 38.35%, 40.1% and 32.83%, respectively.
[0135] The stress-strain constitutive model of concrete under uniaxial compression is of great significance for theoretical analysis and structural design of concrete structures. In addition to being in good agreement with the test results, a reasonable model should also be simple in form, easy to calculate, and have few undetermined parameters. The axial compression segmented constitutive model of concrete proposed by Guo Zhenhai meets these requirements. For simplicity, this paper uses the constitutive model proposed by Guo Zhenhai to analyze the test results. The constitutive model proposed by Guo Zhenhai is shown in formula (9):
[0136]
[0137] Where: y is the ratio of stress to peak stress, y = σ / σ0, dimensionless; x is the ratio of strain to peak strain, x = ε / ε0, dimensionless; a and b are the control parameters of the ascending and descending sections, respectively. The a value is the ratio of the initial tangent modulus to the secant modulus at the peak point, and the b value reflects the area enclosed by the descending curve and the horizontal axis. The smaller the a value or the larger the b value, the smoother the curve, the smaller the area enclosed by the curve and the horizontal axis, the smaller the elastic deformation of the concrete, the lower the residual strength, and the slower the destruction process.
[0138] This embodiment further adopts the uniaxial compressive stress-strain constitutive model to fit the stress-strain curve of RACSCC. The stress-strain curves of each group of RACSCC are fitted to obtain the fitting graph and fitting parameters as shown in FIG. Fig.21 As shown in Table 4. a and b are the fitting parameters of the rising and falling sections of the stress-strain curve, respectively. In Table 4, the correlation coefficient R 2The minimum is 0.9036 and the maximum is 0.9995, indicating that the fitting effect of the model is good; the larger the RCA replacement rate, the smaller a and the larger b; the larger the number of freeze-thaw cycles, the smaller a and the larger b; it means that the slope of the rising section of the curve gradually decreases, the descending section gradually flattens, and the plastic properties of recycled coarse aggregate self-compacting concrete gradually increase; in the four freeze-thaw environments, RC50-H has the largest a and the smallest b, and RC50-M has the smallest a and the largest b.
[0139] Table 4 Fitting parameters a and b
[0140]
[0141] Linear regression fitting is performed on all a and b in Table 4 and the peak stress. The fitting results are shown in Fig. 22 , the regression formulas are shown in formula (10) and formula (11).
[0142]
[0143] Elastic modulus is one of the important evaluation indicators that reflects the internal force of concrete structure and its ability to resist deformation and cracking. The elastic modulus of concrete is calculated according to Formula 7.0.5 in the Standard Method for Testing Physical and Mechanical Properties of Concrete. The elastic modulus change curve of recycled coarse aggregate self-compacting concrete after sulfate freeze-thaw is drawn as follows: Fig.23 shown. Fig.23 The results show that the greater the number of freeze-thaw cycles, the smaller the elastic modulus of recycled coarse aggregate self-compacting concrete. Compared with 0 freeze-thaw cycles, after 125 freeze-thaw cycles, the elastic modulus of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM decreased by 51.98%, 43.59%, 58.99%, 59%, 63.95% and 58.9%, respectively. Fig.23 (a) It can be seen that at the same number of freeze-thaw cycles, the greater the RCA replacement rate, the smaller the elastic modulus of recycled coarse aggregate self-compacting concrete. The main reason for the smaller elastic modulus of RCA concrete is the lower elastic modulus of RCA. The old mortar layer on the RCA surface has many internal defects, its strength is low and its porosity is high, resulting in a low elastic modulus of RCA. Fig.23 (b) It can be seen that the self-compacting concrete with recycled coarse aggregate is more seriously damaged in the sulfate freeze-thaw environment; when the number of freeze-thaw cycles is the same, the elastic modulus of the self-compacting concrete with recycled coarse aggregate in the H type freeze-thaw environment is the largest, and the elastic modulus of the self-compacting concrete with recycled coarse aggregate in the M type freeze-thaw environment is the smallest. 2- Mg 2+ They will react with the hydration products inside the recycled coarse aggregate self-compacting concrete to corrode, causing the structural stability of the recycled coarse aggregate self-compacting concrete to decrease and the elastic modulus to decrease as well.
[0144] Like the elastic modulus, the value of Poisson's ratio can be used to evaluate the internal force, deformation resistance and crack resistance of concrete structures. The Poisson's ratio of recycled coarse aggregate self-compacting concrete is calculated according to the standard method for testing the physical and mechanical properties of concrete. Fig.24 is a graph of the relationship between Poisson's ratio and the number of freeze-thaw cycles. Fig.24 The results showed that the Poisson's ratio of each group of RCSCC decreased with the increase of freeze-thaw cycles; compared with 0 freeze-thaw cycles, after 125 freeze-thaw cycles, the elastic modulus of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM decreased by 31.67%, 31.16%, 37.26%, 33.02%, 37.21% and 34.42%, respectively. Fig.24 (a) shows that the Poisson's ratio of each group of recycled coarse aggregate self-compacting concrete shows a "stratified" phenomenon; when the number of freeze-thaw cycles is the same, the greater the RCA replacement rate, the smaller the Poisson's ratio. Fig.24 (b) shows that when the number of freeze-thaw cycles is the same, the Poisson's ratio of the H type freeze-thaw environment is the largest, and the Poisson's ratio of the M type freeze-thaw environment is the smallest.
[0145] Fig.25 The relationship curves between the peak stress and dynamic elastic modulus of each group of recycled coarse aggregate self-compacting concrete after experiencing different times of sulfate freeze-thaw. Fig.25 It can be seen that the peak stress increases with the increase of dynamic elastic modulus. The peak stress and dynamic elastic modulus are linearly regressed and fitted. The regression equation and fitting graph are obtained as shown in formula (12) and Fig.25 shown.
[0146]
[0147] Fig.26 These are the relationship curves between the peak stress and ultrasonic wave velocity of each group of recycled coarse aggregate self-compacting concrete after experiencing different times of sulfate freeze-thaw. Fig.26 It shows that there is a positive correlation between peak stress and ultrasonic wave velocity. Peak stress and ultrasonic wave velocity have a good linear correlation. The fitting graph and formula are as follows: Fig.26 As shown in formula (13).
[0148]
[0149] The data of mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting tensile strength, elastic modulus and Poisson's ratio were selected to calculate the d of recycled coarse aggregate self-compacting concrete under sulfate freeze-thaw action. i Taking the data of RC50-H as an example, the comprehensive evaluation index of durability of recycled coarse aggregate self-compacting concrete under sulfate freeze-thaw action is calculated.
[0150] Table 5 Test data of RC50-H
[0151]
[0152] (1) Establish an initial durability index matrix.
[0153]
[0154] (2) Standardization of durability indicators.
[0155]
[0156] (3) Establish a weight matrix.
[0157]
[0158] (4) Establish information utility value matrix.
[0159] P=[0.9208 0.9152 0.9173 0.9201 0.9194 0.9034 0.9161] (17)
[0160] (5) Establish an indicator weight matrix.
[0161] K=[0.1348 0.1443 0.1407 0.136 0.1372 0.1644 0.1427] (18)
[0162] (6) Calculate the durability evaluation index matrix.
[0163] D=[1 0.9242 0.8682 0.8205 0.7693 0.7328] T (19)
[0164] Repeat the above steps to calculate the mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting strength, elastic modulus and Poisson's ratio of NC-H, RC100-H, RC50-N, RC50-M and RC50-NM. The calculation results are listed in Table 6.
[0165] Table 6 D calculation results
[0166]
[0167] Figure 7 The variation curves of D of NC-H, RC50-H, RC100-H, RC50-N, RC50-M and RC50-NM with the number of sulfate freeze-thaw cycles are shown. Figure 7In the results, all curves show that the parameter D shows a downward trend with the increase of sulfate freeze-thaw cycles. Under all sulfate freeze-thaw cycles, the D value of NC-H always remains the highest, showing good stability. The D value of RC50-H is second, and the downward trend is relatively gentle, indicating that its performance decreases slowly in sulfate freeze-thaw cycles. The D value of RC100-H decreases the fastest, especially after the number of cycles exceeds 50, the performance decreases more significantly. Compared with RC50-H, the D value of RC50-N is slightly lower, and the downward trend is similar, but the overall performance is slightly inferior to RC50-H. The downward trend of the D value of RC50-M is similar to that of RC50-H, but the decline rate accelerates after the number of sulfate cycles exceeds 50. The D value of RC50-NM is the lowest under all conditions, and the downward trend is the most significant, showing the worst stability. NC-H and RC50-H show good stability in sulfate freeze-thaw cycles, while RC50-NM shows the worst stability. These analyses can help understand the performance changes of recycled coarse aggregate self-compacting concrete under sulfate freeze-thaw cycles and provide a reference for the engineering practice of recycled coarse aggregate self-compacting concrete.
[0168] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete, characterized in that: The following steps are involved: S1. Prepare recycled coarse aggregate self-compacting concrete specimens in which recycled coarse aggregate completely or partially replaces stone according to design requirements; S2, immersing the recycled coarse aggregate self-compacting concrete specimens in a freeze-thaw medium to conduct a freeze-thaw cycle test; S3, measuring damage indicators of recycled coarse aggregate self-compacting concrete specimens, wherein the damage indicators include mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting tensile strength, stress-strain curve, elastic modulus or Poisson's ratio; S4. Compare the damage indicators of self-compacting concrete specimens with different recycled coarse aggregates to obtain recycled coarse aggregate self-compacting concrete specimens with excellent comprehensive performance.
2. A method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1, characterized in that: In S2, the freeze-thaw medium includes water, a 5% by mass Na2SO4 solution, a 5% by mass MgSO4 solution, and a mixed salt solution of 5% by mass Na2SO4 and 5% by mass MgSO4.
3. The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1, characterized in that: In S2, the freeze-thaw cycle test was carried out using a HDK-3 concrete rapid freeze-thaw machine according to the rapid freezing method to ensure that the specimens were always in a saturated freeze-thaw medium state during the freeze-thaw process.
4. The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1, characterized in that: In S4, based on the mass, dynamic elastic modulus, and ultrasonic wave velocity before and after the freeze-thaw cycle, the mass loss rate, dynamic elastic modulus damage value, and ultrasonic wave velocity damage value were calculated to preliminarily evaluate the sulfate freeze-thaw resistance.
5. The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 4, characterized in that: The calculation formulas for mass loss rate, dynamic elastic modulus damage value, and ultrasonic wave velocity damage value are: Where, ΔW N is the mass loss rate after N freeze-thaw cycles, in %; G0 and G N are the mass of recycled coarse aggregate self-compacting concrete before and after the freeze-thaw cycle test N times, in kg; D N is the dynamic elastic modulus damage value after freeze-thaw cycles N times; E0 and E N are the dynamic elastic modulus of recycled coarse aggregate self-compacting concrete before the freeze-thaw cycle test and after N freeze-thaw cycles, in MPa; V N V is the ultrasonic wave velocity damage value after N freeze-thaw cycles; d0 and V dN are the ultrasonic wave velocities of recycled coarse aggregate self-compacting concrete before and after the freeze-thaw cycle test N times, in km·s -1 .
6. The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1, characterized in that: In S4, the evaluation criteria for the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete specimens are as follows: the smaller the mass loss rate, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimens; The smaller the damage value of dynamic elastic modulus, the better the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete specimens; The smaller the ultrasonic wave velocity damage value is, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimen is; The greater the compressive strength, splitting tensile strength and uniaxial compressive strength, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimens; The gentler the change of stress-strain curve, the better the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete specimens; The larger the elastic modulus and Poisson's ratio, the better the sulfate freeze-thaw resistance of the recycled coarse aggregate self-compacting concrete specimens.
7. The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1, characterized in that: In S3, the compressive strength was tested using a SHT4106 microcomputer-controlled electro-hydraulic servo universal testing machine; The splitting strength was tested using a CMT5305 microcomputer-controlled electro-hydraulic servo universal testing machine; The stress-strain curve, elastic modulus and Poisson's ratio were tested by SHT4106 microcomputer-controlled electro-hydraulic servo universal testing machine.
8. The method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 1, characterized in that: In S4, the comprehensive sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete specimens was evaluated based on the durability comprehensive evaluation index D. The smaller the D value, the worse the comprehensive sulfate freeze-thaw resistance.
9. A method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 8, characterized in that: The calculation formula of the durability comprehensive evaluation index D is: D=q1S1+q2S2+q3S3+q4S4+q5S5+q6S6+q7S7; Among them, q1, q2, q3, q4, q5, q6, and q7 are the weight coefficients of S1 to S7, and their values are 0.1348, 0.1443, 0.136, 0.1372, 0.1644, and 0.1427 respectively; S1 to S7 represent the values of mass, dynamic elastic modulus, ultrasonic wave velocity, compressive strength, splitting strength, elastic modulus and Poisson's ratio, respectively.
10. A method for evaluating the sulfate freeze-thaw resistance of recycled coarse aggregate self-compacting concrete according to claim 8 or 9, characterized in that: When the D value is less than 0.75, it means that the recycled coarse aggregate self-compacting concrete specimen is damaged.
Citation Information
Patent Citations
Method for improving quality of recycled coarse aggregate by adopting sulfate erosion-freeze-thaw cycle
CN110922078A
Concrete capable of improving sulfate freezing resistance and test method
CN112358258A
Concrete anti-carbonization durability evaluation method
CN118134298A
Cited By
Method and system for analyzing mechanical properties of hogging moment area of UHPC thin-layer reinforced steel-concrete composite beam
CN120409149A
Mechanical performance analysis method and system for negative moment zone of UHPC thin-layer reinforced steel-concrete composite beams
CN120409149B
Concrete test piece and characterization method for influence of freeze thawing and size on concrete strength
CN120518366A